Pertussis outbreak in southern Ethiopia: challenges of detection, management, and response - Aychiluhim D. Mitiku; Mesele D. Argaw; Binyam F. Desta; Zergu T. Tsegaye; Afework A. Atsa; Bekele B. Tefera; Ephrem Teferi; Deirdre Rogers; Ismael A. Beshir; Asrat G. Alemu; Desta A. Ayesa; Derebe T. Abate; et al. (BMC, 2020)
Abstract Background Despite the availability of effective vaccines, pertussis remains endemic with high fatality rates in low and middle-income countries (LMIC). This study aims to describe an outbreak of pertussis in a health district of Ethiopia. The study highlights the challenges faced by the health system in identifying pertussis cases and appropriately responding to the outbreak at the district level. Methods A descriptive cross-sectional study was conducted using data sourced from the District Public Health Emergency and Management (PHEM) surveillance service and outbreak management field reports. Stratified attack rates and fatality rates for pertussis are described. Systemic problems leading to the outbreak are explored and narrated. A modified CDC pertussis case definition was employed with a polymerase chain reaction used to confirm cases. Results From September 2018 to January 2019, 1840 suspected, probable, and confirmed pertussis cases and six deaths were identified. Pertussis cases ranged from 1 month to 51 years in age. An outbreak occurred in 14 out of the 24 villages of Dara Malo district. The overall attack rate was 1708 per 100,000 population with a fatality rate of 3.3 per 1000 pertussis cases. The highest attack rate of 12,689/100,000 was seen in infants. Among confirmed, probable and suspected pertussis cases, only 41.1% had completed the three-dose pertussis vaccine's primary schedule. The household survey revealed a population coverage of 73.4 and 40.8% for Pentavalent vaccine dose one and three respectively. Investigations suggested the existence of a poor cold chain management system in the study area. Conclusions There is an urgent need to build capacity to strengthen routine vaccination services and improve the maintenance of the vaccine cold chain. Other LMICs are urged to take lessons learned from this outbreak to strengthen their own vaccination programs and capacitate health workers to manage local outbreaks.